Phacoemulsification and Visco-synechiolysis With or Without Trabeculectomy Following Initial Management of Acute Primary Angle Closure: A Comparative Study - Kermani, Mahdi Sharifzadeh; Karimi, Mina Haj-mohammad; Sharifi, Ali; Shadravan, Mahla; Daneshtalab, Arash; Zand, Amin (Journal of Ophthalmic and Vision Research, 2025)
Purpose: To assess the effects of phacoemulsification, visco-synechiolysis, and trabeculectomy on eyes with a recent history of acute primary angle closure (APAC). Methods: In this prospective nonrandomized study, we enrolled patients with cataracts, peripheral anterior synechiae (PAS), and a history of APAC attack managed with medications and laser peripheral iridotomy (LPI) within the past six weeks. Patients without signs of glaucomatous optic neuropathy (GON) underwent phacoemulsification and visco-synechiolysis (PV group). Trabeculectomy was added to this procedure for cases with signs of underlying chronic GON (PVT group). We evaluated best-corrected visual acuity (BCVA), intraocular pressure (IOP), angle opening, PAS extension, and adverse events at baseline and six months postoperatively. Results: The PV and PVT groups comprised 8 and 12 eyes, respectively. At month six, both groups showed significant improvement in BCVA, reduced IOP, and increased Shaffer grading scores compared to baseline (all Ps < 0.05). Extensive PAS (≥180º) significantly decreased at month six in both the PV (P = 0.008) and PVT (P = 0.002) groups compared to baseline. However, its prevalence did not significantly differ between the two groups at baseline (P = 0.288) or six months after surgery (P = 0.881). At month six, IOP was significantly lower in the PVT group than the PV group (10.83 ± 1.40 vs 13.63 ± 2.07 mmHg, P = 0.002). Nevertheless, BCVA and Shaffer grading scores were not different between the two groups at this time point (P = 0.120, and P = 0.891, respectively). No serious complications were observed in any groups during the follow-ups. Conclusion: Patients with cataracts and a recent history of APAC without underlying chronic glaucoma may not receive additional trabeculectomy alongside lens extraction and synechiolysis